2008
DOI: 10.3390/s8085037
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aspens Using High Resolution Aerial Laser Scanning Data and Digital Aerial Images

Abstract: The aim was to use high resolution Aerial Laser Scanning (ALS) data and aerial images to detect European aspen (Populus tremula L.) from among other deciduous trees. The field data consisted of 14 sample plots of 30 m × 30 m size located in the Koli National Park in the North Karelia, Eastern Finland. A Canopy Height Model (CHM) was interpolated from the ALS data with a pulse density of 3.86/m2, low-pass filtered using Height-Based Filtering (HBF) and binarized to create the mask needed to separate the ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In a study by Säynäjoki et al (2008), single aspen trees were detected from dense ALS data. The inventory system was, however, rather complex, including, for instance, visual interpretations by aerial images to separate coniferous trees from deciduous trees.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Säynäjoki et al (2008), single aspen trees were detected from dense ALS data. The inventory system was, however, rather complex, including, for instance, visual interpretations by aerial images to separate coniferous trees from deciduous trees.…”
Section: Introductionmentioning
confidence: 99%
“…in 2005 for another purpose, to develop ALS-based methods for the recognition of large aspens (Säynäjoki et al 2008). Site fertility on the various plots varied from fertile to relatively fertile.…”
Section: Kolimentioning
confidence: 99%
“…Hinsley et al (2002), for example, used ALS data to assess the quality of bird habitats, and Müller et al (2009) observed that ALS was superior to aerial photographs for estimating the abundance of birds in Southeastern Germany. In addition, ALS data have been used, for identifying large aspens (Säynäjoki et al 2008) and stands with high herbaceous plant diversity (Vehmas et al 2009). …”
Section: Remote Sensing and Its Application To The Assessment Of Ecolmentioning
confidence: 99%
“…Remote sensing can be used for measuring various environmental parameters, such as reflectance properties and three-dimensional (3D) structure of vegetation related to biodiversity (e.g., [23,24]). Reflectance properties capture variation between some of the tree species [25,26] as well as tree vigor [27,28]. Various remote sensing data sets (e.g., point clouds derived from airborne laser scanning (ALS) or optical imagery) enable characterizing forest Remote Sens.…”
Section: Introductionmentioning
confidence: 99%
“…2018, 10, 338 3 of 22 structure through height, height variation, and density of the vegetation. ALS data have been used to map and monitor old deciduous trees within stands [26], stands with mixed species and multiple canopy layers [29][30][31][32], site type [33], as well as amount of dead wood [34], and canopy gaps [35], all being related to diversity of forest ecosystem. In addition, sparse ALS data was used by [36] to locate potential wildlife habitats, but concluded that information on shrub and herb layers, important habitat characteristics for game birds studied, was challenging.…”
Section: Introductionmentioning
confidence: 99%